FEATURES OF THE EPICS OF THE “BIRD’S LANGUAGE” SERIES (TAMADDUN NURI JURNALI, 2024)
The article analyzes views on the textual roots of the series of epics “Bird's Language”, polished over centuries. Their fundamental essence and the Islamic-mystical spirit embodied in them are described, aspects of the promoted good ideas related to the era.